Essential updates to the surgical treatment of biliary tract cancer. Issue 4 (22nd May 2019) - Matsukuma, Satoshi; Tokumitsu, Yukio; Shindo, Yoshitaro; Matsui, Hiroto; Nagano, Hiroaki
Abstract: Biliary tract cancer, which includes intrahepatic cholangiocarcinoma, extrahepatic bile duct cancer, gallbladder cancer, and ampullary cancer, is an intractable disease with a dismal prognosis. Prognosis is particularly poor in cases involving vessels or lymph nodes. Hepatobiliary pancreatic surgeons worldwide have consistently focused on improving surgical treatment, perioperative management, and chemotherapy to improve the outcomes of these diseases. There has been significant progress even in the last 2 years (2017 and 2018), such as promising findings reported by studies on the optimal extent of surgical treatment and multi‐institutional randomized controlled trials on adjuvant chemotherapy. We overview the current trends and advancements made in surgical treatment in 2017 and 2018. Abstract : There has been significant progress even in the last 2 years (2017 and 2018), such as promising findings reported by studies on the optimal extent of surgical treatment and multi‐institutional randomized controlled trials on adjuvant chemotherapy. We overview the current trends and advancements made in surgical treatment in 2017 and 2018.